Effect of an eight-week imagery training programme on passing decision-making of young volleyball players - Fortes, L. S.; Freitas-Junior, C. G.; Paes, P. P.; Vieira, L. F.; Nascimento-Júnior, J. R. A.; Alves Araújo Lima-Júnior, D. R.; Ferreira, M. E. C. (International Journal of Sport and Exercise Psychology, 2020)
Background: The passing decision-making performance in volleyball is important because it determines the quality of a team`s attack. However, no study has analysed the effect of imagery training on passing decision-making performance in young volleyball athletes. Purpose: The objective was to analyse the effect of eight weeks of imagery training on passing decision-making performance. Method: Participants were 33 young male athletes (under 17 years [U-17]). Participants were randomly assigned to two groups: experimental (EG, n = 17) and control group (CG, n = 16). The CG watched videos of advertisements, while EG participated in the imagery training. A cognitive-general imagery programme was adopted, that asks the athletes to imagine themselves executing passes during a competitive event (e.g. reception of the service with variations of speed and displacement, pass to middle attacker, pass to other attackers, and pass with projection of the body on the ground). The passing decision-making was evaluated in a simulation of a volleyball official game. The analysis of actions was based on the Game Performance Assessment instrument. A heart rate monitor was adopted as an indicator of the autonomic nervous system response during the sessions for the EG and CG. Results: The results revealed a group versus intervention interaction (p < .01) for the passing decision-making, with improvement only in the EG (p = .01). A statistically significant difference in heart rate was identified between the groups (p = .01), with a higher value in the EG. Conclusions: It was concluded that imagery training enhanced passing decision-making performance.